Perlindungan Hukum Terhadap Pelaku Tindak Pidana yang Mengalami Gangguan Jiwa - Kevin Jerrick Pangestu; I Nyoman Gede Sugiartha; I G. A. A. Gita Pritayanti Dinar (Fakultas Hukum Universitas Warmadewa, 2022)
Mental disorders are the result of several or a group of symptoms that arise in human psychology. People with mental disorders have been stereotyped highly related to criminal acts for a long time, especially violence and threaten the safety and security of those around them. Perpetrators of criminal acts who experience mental disorders are included in the category of persons that had mental disabilities and entitled to more appropriate treatment and protection. It's important to understand more about the responsibility of perpetrators of criminal acts that had mental disorders, as well as about legal protection. The addition of insight, input and additional knowledge are the benefits in the research. The method used by researchers in this study is a normative research method. In the sentencing process, which involves the person who commits a crime that has a mental disorder, the judge is obliged to find and prove whether the perpetrator has an element of accountability, as well as ensure that the perpetrator gets appropriate legal protection. Legal protection is given to the public, especially in this discussion to criminals who experience mental disorders in the hope that the perpetrators can obtain the rights granted by the law itself.